Development and evaluation of a chronic kidney disease risk prediction model using random forest - Mendapara, Krish (Frontiers in Genetics, 2024)
This research aims to advance the detection of Chronic Kidney Disease (CKD) through a novel gene-based predictive model, leveraging recent breakthroughs in gene sequencing. We sourced and merged gene expression profiles of CKD-affected renal tissues from the Gene Expression Omnibus (GEO) database, classifying them into two sets for training and validation in a 7:3 ratio. The training set included 141 CKD and 33 non-CKD specimens, while the validation set had 60 and 14, respectively. The disease risk prediction model was constructed using the training dataset, while the validation dataset confirmed the model's identification capabilities. The development of our predictive model began with evaluating differentially expressed genes (DEGs) between the two groups. We isolated six genes using Lasso and random forest (RF) methods-DUSP1, GADD45B, IFI44L, IFI30, ATF3, and LYZ-which are critical in differentiating CKD from non-CKD tissues. We refined our random forest (RF) model through 10-fold cross-validation, repeated five times, to optimize the mtry parameter. The performance of our model was robust, with an average AUC of 0.979 across the folds, translating to a 91.18% accuracy. Validation tests further confirmed its efficacy, with a 94.59% accuracy and an AUC of 0.990. External validation using dataset GSE180394 yielded an AUC of 0.913, 89.83% accuracy, and a sensitivity rate of 0.889, underscoring the model's reliability. In summary, the study identified critical genetic biomarkers and successfully developed a novel disease risk prediction model for CKD. This model can serve as a valuable tool for CKD disease risk assessment and contribute significantly to CKD identification.1. Integration of various GEO datasets into a comprehensive sample dataset. 2. Examination of biomarkers for CKD within kidney tissue specimens. 3. A collaborative investigation utilizing Lasso and random forest methods to identify CKD biomarkers. 4. An innovative and robust CKD disease risk prediction model was created, employing a random forest algorithm and utilizing six critical genes (DUSP1, GADD45B, IFI44L, IFI30, ATF3, and LYZ). 5. Thorough testing of the models using both a validation dataset and an external validation dataset.